Use of nasal samples and genom amplification methods for detection of respiratory viruses in infants with acute lower respiratory tract infection - Bulut, Yasemin; Sen, Yasar; Goedekmerdan, Ahmet; Oezdiller, Suekran; Toraman, Zuelal Asci (Tubitak Scientific & Technological Research Council Turkey, 2007)
Aim: The aim of this study was to evaluate the use of genome amplification methods [polymerase chain reaction (PCR) and reverse transcription (RT)-PCR] for detection of common respiratory viruses (RSV: respiratory syncytial virus, PIV3: parainfluenza virus 3, IVA: influenza virus type A, IVB: influenza virus type B and adenovirus) in nasal wash specimens of infants with acute lower respiratory tract infection (ALRI). Materials and Methods: The nasal and serum samples taken from 90 infants with ALRI were analyzed by genome amplification methods and ELISA. Results: In ELISA, specific IgM to only one virus and to multiple viruses was present in 39 (43.3%) and 7 (7.7%) of the serum samples, respectively. Therefore, IgM positivity to at least one virus was detected in 46 (51.1%) of the serum samples. In the genome amplification methods in nasal samples, 62 (68.8%) of these samples were positive for only one virus, whereas 9 (10%) of the samples were found to be positive for multiple viruses. Therefore, a total of 71 (78.8%) samples were accepted as positive with at least one virus. Conclusions: As a result, we recommend use of the genome amplification methods in nasal wash specimens for diagnosis of the respiratory viruses in ALRI infants.
Keywords: acute lower respiratory tract infection; ALRI; infant; PCR; respiratory viruses